Characterization of Emergency Department Rabies Post-Exposure Prophylaxis Procedures with an Infectious Diseases Clinic Referral Process. (February 2022) - Frederickson, Jessica J.; Monroe, Alexandra K.; Hall, Gregory A.; Weant, Kyle A.
Purpose: Rabies post-exposure prophylaxis (rPEP) in the emergency department (ED) is associated with high costs, complicated administration protocols, and a time-sensitive vaccination series that often requires ED follow-up visits for subsequent vaccine administration. This study sought to characterize the number of redirected vaccine administrations in those patients referred to ID Clinic, guideline compliance, and opportunities for improvement.Methods: Retrospective chart review of adult and pediatric patients presenting to the ED from 2016 to 2019 and prescribed rabies immunoglobulin.Results: Of the 89 patients included, 66.3% were referred to ID Clinic. Those referred to clinic had significantly fewer average visits to the ED for repeat vaccination ( P  < .001). Of the 177 vaccinations prescribed for patients referred, 105 were administered in clinic. Overall, having insurance significantly increased the odds of completing the prescribed vaccination series (Odds Ratio (OR) = 4.34, 95% Confidence Interval (CI) = 1.34 to 15.52). Among those patients referred to clinic, having insurance significantly increased the odds of receiving any follow-up doses in clinic (OR = 6.00, 95% CI = 1.48 to 25.98), receiving all of their prescribed follow-up doses in clinic (OR = 10.00, 95% CI = 1.72 to 190.80), and completing the entirety of their vaccination series (OR = 5.89, 95% CI = 1.50 to 26.21).Conclusions: The use of an ID Clinic referral process for rPEP resulted in a significant reduction in the average number of visits to the ED for repeat vaccination, hence avoiding 105 ED visits. Insurance status was a significant factor in both the utilization of the ID Clinic referral system and overall completion of the vaccination series. Future research should explore workflows inclusive of both ED care and outpatient follow-up, care plans for the uninsured, and mechanisms to limit the number of patients that fail to complete the recommended vaccination series.